Effect of Fundamental Factors on Stock Return (On LQ-45 Index Companies In Indonesia Stock Exchange 2017-2020) - Mai Simahatie; Lakharis Inuzula (PT. Radja Intercontinental Publishing, 2022)
This research is an associative research with a quantitative approach.The use of a quantitative approach in this study is intended to test the hypothesis by using statistical calculations to examine the effect of the independent variable on the dependent variable under study. This research will be conducted on the Indonesia Stock Exchange through the official IDX website, namely: http/www.idx.co.id. This research was conducted from July 2021 to December 2021.Typethe data used in this study is quantitative data, namely data measured on a numerical scale (numbers). The population used in this study are companies on the LQ-45 index listed on the Indonesia Stock Exchange from 2017 - 2020, where there are 45 LQ-45 index issuers which will change every 6 months or the period of February and August every year. year. The sampling technique in this study was purposive sampling which was selected based on certain criteria in accordance with the research objectives.